Kif3a regulates planar polarization of auditory hair cells through both ciliary and non-ciliary mechanisms - Sipe, Conor W. (Company of Biologists, 2011)
Auditory hair cells represent one of the most prominent examples of epithelial planar polarity. In the auditory sensory epithelium, planar polarity of individual hair cells is defined by their V-shaped hair bundle, the mechanotransduction organelle located on the apical surface. At the tissue level, all hair cells display uniform planar polarity across the epithelium. Although it is known that tissue planar polarity is controlled by non-canonical Wnt/planar cell polarity (PCP) signaling, the hair cell-intrinsic polarity machinery that establishes the V-shape of the hair bundle is poorly understood. Here, we show that the microtubule motor subunit Kif3a regulates hair cell polarization through both ciliary and non-ciliary mechanisms. Disruption of Kif3a in the inner ear led to absence of the kinocilium, a shortened cochlear duct and flattened hair bundle morphology. Moreover, basal bodies are mispositioned along both the apicobasal and planar polarity axes of mutant hair cells, and hair bundle orientation was uncoupled from the basal body position. We show that a non-ciliary function of Kif3a regulates localized cortical activity of p21-activated kinases (PAK), which in turn controls basal body positioning in hair cells. Our results demonstrate that Kif3a-PAK signaling coordinates planar polarization of the hair bundle and the basal body in hair cells, and establish Kif3a as a key component of the hair cell-intrinsic polarity machinery, which acts in concert with the tissue polarity pathway.